Familial aggregation of idiopathic dilated cardiomyopathy: clinical features and pedigree analysis in 14 families. Issue 2 (February 1993) - Zachara, E; Caforio, A L; Carboni, G P; Pellegrini, A; Pompili, A; Del Porto, G; Sciarra, A; Bosman, C; Boldrini, R; Prati, P L
Abstract : OBJECTIVE–A recent prospective study in patients with dilated cardiomyopathy has reported that the disease is familial in at least 20% of cases, but the pattern of inheritance could not be ascertained. The presence of an autosomal dominant pattern, such as seen in hypertrophic cardiomyopathy, could make it possible to search for single gene defects with linkage analysis, whereas polygenic inheritance would be consistent with the autoimmune hypothesis. To assess the pattern of inheritance, we retrospectively identified patients with familial disease and assessed their first degree relatives (parents, siblings and children) for dilated cardiomyopathy. DESIGN AND PATIENTS–The family history of 105 consecutive patients with dilated cardiomyopathy was reviewed and 14 who had at least one first degree relative with documented disease were identified as probands. Their healthy relatives (109) were studied by physical examination, electrocardiography, M mode and cross sectional echocardiography, and were classified as unequivocally normal or as potential carriers. The potential carriers had abnormal electrocardiography with either at least one echocardiographic measurement of left ventricular cavity dimension or percentage fractional shortening outside 2 SDs of normal values (based on age and body surface area). The potential carriers underwent 24 hour Holter monitoring and maximal treadmill exercise. RESULTS AND CONCLUSION–Twenty three relatives (21%) were classified as potential carriers: 12 had an increased left ventricular end diastolic dimension, with reduced percentage fractional shortening in three; 11 had an abnormal electrocardiogram and increased end diastolic dimension, with reduced percentage fractional shortening in five. Such abnormalities were very mild and follow up is necessary to find whether such changes represent early disease. Pedigree analysis was most consistent with polygenic inheritance.